Perkembangan Fonologi Bahasa Jawa Banyumasan Anak Usia Dini melalui Pertunjukan Wayang Bebek - Joyce Artha Kafi; Octaria Putri Nurharyani; Ika Oktaviana (HUMANIKA, 2026)
This study aims to describe the phonological development of Banyumasan Javanese in children aged 6–8 years through exposure to the traditional performance Wayang Bebek Banyumas. The research employed a qualitative descriptive method with a psycholinguistic approach. The subjects were 5 first-grade students of SD Muhammadiyah Cipete. Data were collected through observation, interviews, and audio-video recordings of children’s pronunciations of Banyumasan Javanese vocabulary before and after watching the Wayang Bebek Banyumas performance entitled Balapan Renang. The data were analyzed using an interactive analysis model by comparing phonetic transcriptions across the two conditions. The results show a clear improvement in children’s phonological abilities after the performance, indicated by increased accuracy and consistency in pronunciation, particularly in producing Banyumasan-specific sounds such as vowels, nasal consonants, and glottal stops. Children also demonstrated better imitation of onomatopoeic sounds relevant to the cultural context. These findings suggest that Wayang Bebek Banyumas serves as an effective linguistic stimulus that supports children’s phonological development while contributing to the preservation of Banyumasan Javanese as a regional language.